Description of Hemicycliophora cardamomi sp. n. (Nematoda: Hemicycliophoridae) associated with Amomum longiligulare T.L. Wu and a web-based key for the identification of Hemicycliophora spp. (14th January 2021) - Nguyen, H.T.; Trinh, Q.P.; Couvreur, M.; Nguyen, T.D.; Bert, W.
Abstract: During a survey of plant diseases in the Central Highlands of Vietnam, a new plant-parasitic nematode, Hemicycliophora cardamomi sp. n., was discovered in the growing areas of Amomum longiligulare, a valuable medicinal plant with high economical value. The new species is characterized by a cuticular sheath loosely fitting body; a labial region continuous to the body contour bearing 3 annuli; a lateral field frequently marked by a discontinuous single line with indistinct additional short lines in some parts along the body; a modified vulval lip with an anterior lip c. 4 annuli long; and a post-vulval body tapering to a pointed tail tip with an abrupt constriction at the last third of the post-vulval body. Morphology and molecular characterizations of D2-D3 expansion segment of 28S rRNA, ITS, and COI mtDNA gene regions clearly distinguish the new species from all other 133 known species. This study also provides a newly developed web-based key for the identification of Hemicycliophora spp. in order to accelerate the identification process, to minimize the increasing error load associated with larger datasets, and to avoid any dependence on a single starting entry. This key includes both an existing Bray–Curtis similarity measure and a newly developed similarity formula.